Bisexuality, intimate citizenship and psychosocial well-being: Perceptions of bisexual activists in Portugal - Esteves, M.; Moleiro, C. (LGBTQI+ Studies | Preconference for the 19th General Meeting of the European Association of Social Psychology, 2023)
In Southern Europe LGBTQI+ communities have historically made a clear contribution to the conquest for equality and for the recognition of sexual and reproductive rights by providing people with non-heterosexual sexualities with safety spaces and networks of care, free from cisnormativity and heteronormativity. The everyday experiences of LGBTQI+ people delimited by a legislative framework and by social policies allow us to think about the notion of intimate citizenship at the theoretical and practical level by invoking the idea of micropolitics of intimacy (Santos, 2018; Andreouli, 2019). While the relevance of these communities for the LGBTI+ population is unquestionable (Formby, 2017), studies indicate that these spaces are not exempt from contradictions and tensions between the different letters that make up the acronym, revealing in certain circumstances relations of subordination and thus not always guaranteeing the psychosocial well-being that LGBTI+ communities set out to achieve (Fox & Ore, 2010; Rust, 2001). This is the case of bisexuality where the lack of public understanding of bisexuality may mean that bisexual individuals experience greater levels of minority stress than lesbian and gay people, whose sexualities are often seen as more 'authentic' (Angelides, 2001 Jorm, Korten, Rodgers, Jacomb, & Christensen, 2002; Oxley & Lucius, 2000). Bisexuality has been consigned throughout history to a place of invisibility and silencing and some authors have even pointed that operates an epistemic erasure project (Yoshino, 2010). For this reason, bisexual self-defined people seek and create bi communities and spaces, within LGBTQ+ communities or outside them, free from violence, where they can express their sexuality fully and safely, and in this way, resisting not only in individual terms but also in political terms (Monro, 2015; Hemmings, 1995;2002). This presentation aims to reflect on the relationship between bisexuality, intimate citizenship, and psychosocial well-being in contemporary Portuguese society from the lens of critical psychology. We will present results from a qualitative research, anchored in an ongoing PhD project. With a focus on the perceptions of bisexual activists in Portugal. The results allow us to the reflection about perceptions about the bisexual communities in Portugal, which elements of tension are identified within the LGBTI+ communities and what are the discourses about the creation of a autonomous spaces for people who self-identify with bisexuality. The study also shows that the need for acceptance and recognition leads to the creation of informal care networks outside LGBTQ+ communities (Maliepaard, 2017; 2018) and an attempt to resist normative principles of gender and sexuality that endure both in society at large and within LGBTQ+ spaces.